alright I can help!
so to find the two values of x that are roots of the equation we need to put the variables all on one side so that we can set up the quadratic formula.
3x^2+2x-5=0 (the -3x^2 becomes positive when moved across the equal sign)
now we can set up the quadratic formula. the equation is x= (-b+-(sqrt of b^2 -4ac))/ 2a
so now we just plug in our variables.
x= (-2+-(sqrt of 2^2 -4×3×-5))/ 2×3
x= (-2+-8)/6
now we just seperate the equations so that we have the two roots. and then just solve!
x= (-2-8)/6 -> x= -5/3
x= (-2+8)/6 -> x=1
hope this helps! best wishes and best of luck!!